Why Riders Break the Rules: A Structural Equation Modeling Approach to Traffic Violations in a Developing Region - Yusi Irawati, Desrina; Sri Widari , Nyoman; Ruben Canariesa , Armadeo (Spektrum Industri, 2025)
Traffic violations remain a major contributor to road traffic accidents in Indonesia. Despite government initiatives, limited research has examined the psychological and contextual factors driving this behavior. This study extends the Theory of Planned Behavior (TPB) by incorporating risk perception, habit, emotional condition, environmental condition, and legal knowledge and awareness. A structured questionnaire (N=100) was administered to motorcyclists and/or car drivers in East Java; items were derived from established scales and refined using field observations and a pilot test. Respondents were selected using stratified area sampling to ensure relevance. Data were analyzed using PLS-SEM (SmartPLS). Key findings: attitude and perceived behavioral control significantly predicted behavioral intention; intention strongly predicted actual violation behavior; risk perception negatively predicted permissive attitudes. Habit, subjective norms, emotional and environmental conditions, and legal knowledge were not significant predictors. The study contributes theoretically by refining TPB with risk perception as an antecedent of attitude, and practically by suggesting interventions targeting attitudes and risk awareness supported by technology-assisted enforcement in developing-country contexts.